Radiographic dilemma of four systemic bone diseases: rickets, osteomalacia, renal osteodystrophy, and hypophosphatemic rickets (literature review) - Rahasdini, Puri; Epsilawati, Lusi (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: Rickets, osteomalacia, renal osteodystrophy, and hypophosphatemic rickets are systemic diseases that have the same characteristics, namely the condition of bone softening or weak bone conditions. This condition is caused by low levels of calcium and phosphorus in the bones. As a result, the bones become of poor quality, which can be seen histologically in the form of a picture of bone osteoid that is less calcified. However, the etiology of the causes of abnormalities in these four diseases is different, and in particular, the picture in the radiograph certainly has its own character. Review: The purpose of writing this article is to learn more about the special characteristics of these four systemic diseases. The writing method used is a narrative literature review. This article will discuss the four types of systemic diseases, starting from the definition, clinical appearance, appearance in radiographs, and the characteristics of each type. The results of the characterization that has been carried out indicate that, in general, radiography and other imaging methods are indeed difficult to distinguish because they have the same symptoms, but at the beginning of the case, the picture can be distinguished. Conclusion: The conclusion that can be drawn from this article is that between rickets, osteomalacia, renal osteodystrophy, and hypophosphatemic rickets, there are specific characteristics that are the main key in recognizing each abnormality, especially radiographically, that can be recognized.